IEEE 802.11 roaming and authentication in wireless LAN - Minghui Shi (IEEE Wireless communications)
A wireless LAN service integration architecture based on current wireless LAN hot spots is proposed so that migration to a new service becomes easier and cost effective. The proposed architecture offers wireless LAN seamless roaming in wireless LAN/cellular mobile networks. In addition, a link-layer-assisted mobile IP handoff mechanism is introduced to improve the network/domain switching quality in terms of handoff delay and packet loss. An application layer end-to-end authentication and key negotiation scheme is proposed to overcome the open-air connection problem existing in wireless LAN deployment. The scheme provides a general solution for Internet applications running on a mobile station under various authentication scenarios and keeps the communications private to other wireless LAN users and foreign network. A functional demonstration of the scheme is given. The research results can contribute to rapid deployment of wireless LANs.